G289(P) A systematic review of household and family alcohol misuse and adolescent behavioural outcomes in low- and middle-income countries. (May 2019) - Jokinen, T; Alexander, EC; Manikam, L; Huq, T; Benjumea, D; Das, I; Davidson, L
Abstract : Aims: This systematic review seeks to collate studies from low- and middle-income countries (LMICs) to identify links between consumption of alcohol by household members and adolescent behavioural health outcomes. Methods: Five databases (Medline, EMBASE, OVID Global Health, Cochrane Library and PsycInfo) were searched from 1990–2018, including terms 'alcohol use', 'household', 'adolescent' and 'neurodevelopmental/behavioural outcome(s)'. Studies were eligible if they explicitly investigated alcohol misuse (or synonyms e.g. abuse, dependency), with misuse being defined as a pattern of alcohol consumption putting the individual or dependents at risk of physical and mental health problems. Eligibility was also assessed for participants, behavioural outcomes, and language. A Cochrane LMIC filter was utilised to screen abstracts and World Bank definitions were used to define LMICs. Quality appraisal utilised the National Institute of Heart, Lung and Blood (NIHLB) Quality Assessment Tools. Since the range of outcomes differed significantly by age group, we split the review into studies of children and studies of adolescents. Studies of the impact of household alcohol misuse on adolescents are included in this paper. Adolescents were defined as being within 10–18 years of age. Results: Searches identified 24 844 studies across five databases. After filtering and screening processes, 22 were included in the review. Across the studies, 39 428 participants were included, from 12 different LMICs. Studies assessed parental exposure (8 studies), family (5), the caregiver (4), paternal exposure (3), and maternal and household exposure (one each). Behavioural outcomes assessed included suicidal ideation and behaviour, which showed a positive association in all five relevant studies; depression and anxiety disorders (four studies, all with a positive association); substance use (excluding alcohol) (7); problem behaviour (3); emotional problems (2); teenage pregnancy (3); and self-harm (1). Conclusions: Despite a variety of settings and designs, this review found a significant association between exposure to household alcohol misuse and adverse adolescent behavioural outcomes, including a range of mental health disorders, problem behaviours, and suicidality. The mechanisms through which exposure to household alcohol misuse may lead to adverse adolescent outcomes may be numerous and complex. Further prospective studies, with careful quantification of amounts of alcohol consumption, are called for.